(untitled) (ALBACORE Jurnal Penelitian Perikanan Laut, 2026)
One of the fishing gear widely used by fisherman in Banten Bay is bottom mini trawl which called jaring arad. The main problem in “jaring arad” fisheries is high bycatch and low selectivity of fishing gear. One effort to reduce high bycatch at jaring arad is the implementation of Turtle Excluder Device (TED. Accordingly, this study aimed to examine community perceptions of the Turtle Excluder Device (TED). Data were collected through interviews with 25 respondents, and the findings were subsequently analyzed using descriptive statistical methods. Research results indicate that 67% of fishermen disagree with the prohibition of jaring arad. However, one of the obstacles to use Turtle Excluder Device (TED) is the limited knowledge and understanding fishers have of the technology. Based on the interview results using the questionnaire, it was found that 61% of the fisherman who participated in the outreach activity had never heard of the TED device, while only 39% had heard of it. After receiving an explanation during the outreach activity about the use of TED, the majority of participating fishers were willing to try it. Based on the survey, 82% of the fishermen were willing to try the Turtle Excluder Device (TED). Key words: bycatch, jaring arad, selectivity, Turtle Excluder Device